Slovakia's Introduction of a Flat Tax as Part of Wider Economic Reforms - Brook, Anne-Marie (OECD Economics Department Working Papers, 2005)
Slovakia's fundamental tax reform of 2004 considerably improved the simplicity and efficiency of the tax system by eliminating exemptions and special regimes and setting the rates for the personal income tax (PIT), the corporate income tax (CIT) and the value added tax (VAT) all equal to 19%. This paper assesses the impact of this reform in the context of Slovakia's wider package of economic reforms. With respect to economic efficiency, the two key conclusions are as follows: First, the reforms are expected to improve both the level and efficiency of capital investment in Slovakia - although further improvements could be made by eliminating the double taxation on projects financed by retained profits. Second, the combination of the tax and social benefit reforms has enhanced the incentives for unemployed workers to seek work, which should result in higher labour supply. Labour demand should also have increased, thanks to the more flexible labour market.